Notes on the Toxorhynchites of Mexico: redescription of Tx. moctezuma (Dyar & Knab) and new record for Tx. grandiosus (Williston) in Veracruz (Diptera: Culicidae) - Mendez-Andrade, Alejandro; Rivera-García, Karina D.; Ibáñez-Bernal, Sergio (Zootaxa, 2019)
Description of the pupa and redescriptions of the larva, female, male and male genitalia of Toxorhynchites (Lynchiella) moctezuma (Dyar & Knab) are presented based on specimens from Mexico, providing information that helps to distinguish this species from other species within the subgenus Lynchiella. Additionally, we report the first finding of Tx. (Lyn.) grandiosus (Williston) in the state of Veracruz, Mexico.